(untitled) (Research, Society and Development, 2024)
COVID-19 is an infectious disease caused by the coronavirus SARS-CoV-2 which presents a variable but potentially serious clinical picture in some individuals. Many of these required long periods of hospitalization and continued to have sequelae even after discharge. Among them, pulmonary diseases can be mentioned, requiring specialized follow-up. The follow-up time after discharge became the object of this study. Objective: To identify, through data collection from the pulmonology outpatient clinic, the follow-up time after medical discharge from both the medical clinic ward and the emergency room of a secondary hospital, within the group of patients who presented severe cases of COVID-19. Methods: Observational, analytical, cross-sectional and retrospective study in which epidemiological and clinical data were analyzed through electronic medical records attended at the pulmonology outpatient clinic of a secondary hospital who met the study’s eligibility criteria. Results: 57 patients were analyzed, the majority of whom were female, with a mean age of 56.65 years. All the patients were referred for outpatient follow-up and 91.23% were followed up. The average length of outpatient follow-up was 27.29 weeks. Conclusion: A longer follow-up period was observed for these patients, most of whom did not present long-term sequelae.